2014
DOI: 10.1111/glob.12050
|View full text |Cite
|
Sign up to set email alerts
|

Transnational healthcare seeking: how ageing Taiwanese return migrants view homeland public benefits

Abstract: In this article, I argue that, by offering ageing return migrants new opportunities both to organize their lives and to rethink their social attachments, the extension of public healthcare in Taiwan constitutes a new contextual feature of the transnational social field bridging Taiwan and the USA. I use the concept of ‘transnational healthcare seeking’ to describe how returning seniors try to maintain their physical, psychological and social well‐being by accessing the benefits of public healthcare available i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…However, as shown by Vathi and King (), this has been completely overlooked in policy‐making on return both in the host and origin countries. Regardless of the definitive choice of the final resting place, political efforts on both sides of migration should aim at sharing financial and social responsibility (international co‐responsibility) for providing healthcare to older migrants (Sun, ) in order to guarantee ageing individuals a good quality of life during their old age and facilitate transnational living arrangements.…”
Section: Final Remarksmentioning
confidence: 99%
“…However, as shown by Vathi and King (), this has been completely overlooked in policy‐making on return both in the host and origin countries. Regardless of the definitive choice of the final resting place, political efforts on both sides of migration should aim at sharing financial and social responsibility (international co‐responsibility) for providing healthcare to older migrants (Sun, ) in order to guarantee ageing individuals a good quality of life during their old age and facilitate transnational living arrangements.…”
Section: Final Remarksmentioning
confidence: 99%
“…It has added one more component to the commodification and globalization of the 'intimate industries', such as beautification, international adoption, retirement, marriage, sex tourism, and sex work. It locates intimate and affective labour in global care chains through multiple, sometimes interlocking, circulating networks (Constable 2009;Deomampo 2013;Dragojlovic 2015;Kim 2015;Sun 2014;Sunanta 2014;Yeates 2009). While reproduction appears a private and intimate affair, it is bound up in national policies (for example towards abortion, adoption, provision of contraception, family sizes and one-child families), in what has been described as a 'global market of commercial fertility' or of 'cross-border reproductive care' (Prasad 2008: 37; see also Inhorn 2011;Payne 2015).…”
mentioning
confidence: 99%
“…Some research highlights that return migration becomes an undesirable option for long-term ageing migrants who spend many of their working years outside their homeland since they have been accustomed to the material and social life in their host societies (Zontini 2014). Other studies show that returning to their homeland helps older migrants pursue a traditional lifestyle and acquire affordable physical and medical care needed to sustain themselves (Gilbertson 2009;Sun 2014b). Despite this increasing scholarly attention to ageing returnees, few studies have carefully examined how these returnees construct their social belonging as they are entering or have entered a later life stage.…”
Section: Research On Ageing and Return Migrationmentioning
confidence: 99%
“…For example, some recent studies found that older people who initially had come to host societies as labour migrants had a hard time adapting to the life in their home societies and were thus reluctant to move back (Hunter 2011;Zontini 2014;Erdal and Ezzati 2015). Likewise, studies of return migration suggest that a group of older expatriates circulates to their homeland to situate themselves in communities where they feel socially and culturally comfortable (Gilbertson 2009;Sun 2014b). Nevertheless, both of these lines of study typically frame ageing people as care seekers who utilise migration as the means to secure different types of support, but do not pay equal attention to the ways in which ageing migrants consider their social membership in the country where they settle, permanently or temporarily, in later life.…”
mentioning
confidence: 99%